Influence of nitrogen at different soil depths on crop health indices and yield of rice - Chandana, B; Shankar, T; Jagadish, G; Majumder, S; Sarkar, S (Plant Science Today, 2026)
Nitrogen plays the most crucial role in the health status and yield of rice. Magnitudes of two crop health indicators, i.e., normalised difference vegetation index (NDVI) and soil plant analysis development (SPAD) values, depend on the availability of nitrogen in the soil. In coarse-textured soils, where the leaching loss of nitrogen is a major concern, the availability of nitrogen in various depths plays a prominent role in crop health indicators as well as grain yield. Rainfall amounting to 398.8 and 189.3 mm, respectively, during 0–30 and 31–50 days after transplanting (DAT) caused the presence of a notable amount of nitrogen at 40 cm depth. The influence of nitrogen levels on both NDVI and SPAD values was assessed in all observation dates (30, 50, 70 and 90 DAT) through regression analysis. The best possible relationship in terms of the coefficient of determination (R2) value was recorded on 30 DAT. Interestingly, on that day, nitrogen at 40 cm depth showed a higher R2 value (0.81) in relation to NDVI over the nitrogen at 15 cm depth (R2 = 0.78). The relationship between soil nitrogen and SPAD was also strongest on 30 DAT and the R2 values were 0.78 and 0.77 against nitrogen availability, respectively, at 15 and 40 cm depths. Grain yield increased continuously with an increase in nitrogen level till the N200 treatment. After attaining the plateau (5.27 Mg ha-1) at N200, the same decreased marginally at N240. Available nitrogen at both depths strongly influenced the grain yield, with R2 values of 0.88 and 0.86 for nitrogen availability at 15 and 40 cm depths, respectively.